2021
DOI: 10.3390/microorganisms9112337
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Drug Susceptibility Testing of Neisseria gonorrhoeae Using Isothermal Microcalorimetry

Abstract: Background: Gonorrhea is a frequently encountered sexually transmitted disease that results in urethritis and can further lead to pelvic inflammatory disease, infertility, and possibly disseminated gonococcal infections. Thus, it must be diagnosed promptly and accurately. In addition, drug susceptibility testing should be performed rapidly as well. Unfortunately, Neisseria gonorrhoea is a fastidious microorganism that is difficult to grow and requires culturing in an opaque medium. Methods: Here, we used isoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Microcalorimetry has been used to determine antimicrobial susceptibility in different organisms and the results obtained so far look are overall in agreement with results obtained with conventional susceptibility tests (62)(63)(64)(65)(66)(67)(68).…”
Section: Alternative Methods For Susceptibility Testingsupporting
confidence: 73%
“…Microcalorimetry has been used to determine antimicrobial susceptibility in different organisms and the results obtained so far look are overall in agreement with results obtained with conventional susceptibility tests (62)(63)(64)(65)(66)(67)(68).…”
Section: Alternative Methods For Susceptibility Testingsupporting
confidence: 73%
“…Baldoni et al showed the differences in the heat flow curves generated by MRSA and MSSA strains (12). Also, Grütter et al investigated detection and drug susceptibility testing in two different strains of Neisseria gonorrhoeae through isothermal microcalorimetry, and highlighted the differences found in the thermograms between strains of the same organism (13). These results suggest that characterization of the thermogram profiles could facilitate the identification of the microorganism causing an infection, including its level of susceptibility to antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue collects examples of quantitative IMC analyses which address microbial growth in various contexts. Grütter et al demonstrate that IMC can be used as a diagnostic tool in urethritis caused by Neisseria gonorrhoea , a pathogen which is difficult to culture for diagnostic purposes [ 7 ]. With IMC, the microorganism is detectable at concentrations as low as 1 CFU·mL −1 , revealing both an organism-specific signature in the heat flow curves and its drug susceptibility.…”
mentioning
confidence: 99%